A comparative analysis of Japanese language learners' motivation in Australia and Korea. Issue 4 (2nd October 2018) - Nakamura, Toshiyuki
ABSTRACT: A growing amount of research has recently focused on the significant role of second language learners' future self-representations in their learning motivation. This article analyses Japanese language learners' motivational characteristics, utilizing data collected from interviews with 26 university students in Australia and South Korea. A comparison between these two contrastive social contexts revealed that interest in Japanese language/culture may be a vital source for motivational intensity to learn the language in both Australian and Korean contexts, whereas the role of L2 self does not appear to be identical in both contexts. Many Australian learners' positive learning experiences seem to help evolve their initial interests in Japanese language/culture and construct their ideal/feared self-images as Japanese users, which contribute to their high motivational intensity to learn the language. On the other hand, some Korean learners' learning experiences appear to have a negative impact on the construction of their ideal Japanese self-representations in the future, and thus, lead to their low motivational intensity. This article also points to the importance of understanding the learners' perceived distance from the target language and culture, and how this may play both a motivating as well as a de-motivating role.